Built Heritage Attractions in Cultural Tourism: the case of Al - Mustansiriya Madrassa, Baghdad - Al-Obaidi, Huda Adil Abdulhameed; Al-Tameemi, Osamah AbdulMunem (Al-Nahrain Journal for Engineering Sciences, 2019)
This research deals with the subject of Built heritage attractions in Muslim historical building, for what it represents, as an element dealing with Cultural tourism, in the process of developing tourism industry of the city._x000D_ The location of Mustansiriya Madrassa in Baghdad’s commercial district could make it a profitable investment project to revive a cultural, artistic and tourist centre that could make it a cultural Tourism haven._x000D_ The problem emerges through, how the role of built heritage to attract tourists in order to give vitality and liveability to the cultural tourism destination such as Al - Mustansiriya Madrassa which is one of the most popular heritage destinations, a historic school building situated in the ancient Abbasid district of Rusafa in the very heart of Baghdad._x000D_ Therefore, the research’s aim is to shed light on the heritage attraction as a mean to clarify the meaning of Cultural Tourism and specifying its definition._x000D_ This research explains how the built heritage plays an important role in tourism in general and in the cultural tourism in particular because they attract tourists and provides a sustainable economic resource through its inclusion of values that make it distinct from other sources of attraction.